The pursuit of standardization in domestic violence social work: A multiple case study of how the idea of using risk assessment tools is manifested and processed in the Swedish social services. (May 2019) - Skillmark, Mikael; Agevall Gross, Lotta; Kjellgren, Cecilia; Denvall, Verner
This multiple case study examines how the idea of using risk assessment tools is manifested and processed in Swedish social services. Based on the analysis of interviews with different stakeholders and of organizational documents in two social service organizations, we investigate the actors who control local risk assessment practices. The findings illustrate that a relatively small group of social workers in the organizations have been able to forward their claims and decide how risk assessment work should be carried out without much intrusion from local managers or politicians. The findings also validate other studies that found that increased standardization can strengthen social workers' ability to perform their professional task rather than lead to de-professionalization. This article ends with a discussion of what risk assessment practices might mean for domestic violence victims.